2019
DOI: 10.1111/jipb.12818
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin repression of axillary bud formation in Arabidopsis by modulation of DELLA‐SPL9 complex activity

Abstract: The formation of lateral branches has an important and fundamental contribution to the remarkable developmental plasticity of plants, which allows plants to alter their architecture to adapt to the challenging environment conditions. The Gibberellin (GA) phytohormones have been known to regulate the outgrowth of axillary meristems (AMs), but the specific molecular mechanisms remain unclear. Here we show that DELLA proteins regulate axillary bud formation by interacting and regulating the DNA‐binding ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…The precise mechanisms by which LAS regulates these processes remain elusive; however, the mutation in the LAS ortholog in tomato affects the levels of hormones involved in shoot meristem activity, such as auxin, gibberellin (GA), and cytokinin [44,45]. Recently, it has been shown that the LAS protein binds to the promoter of GA2ox4, which encodes a GA deactivation enzyme, and promotes its expression [46]. These results raise the possibility that LAS reduces the levels of GA in the boundary region to promote shoot meristem activity, thereby contributing independently of STM, KNAT6, and BLR to the process downstream of the CUC genes.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms by which LAS regulates these processes remain elusive; however, the mutation in the LAS ortholog in tomato affects the levels of hormones involved in shoot meristem activity, such as auxin, gibberellin (GA), and cytokinin [44,45]. Recently, it has been shown that the LAS protein binds to the promoter of GA2ox4, which encodes a GA deactivation enzyme, and promotes its expression [46]. These results raise the possibility that LAS reduces the levels of GA in the boundary region to promote shoot meristem activity, thereby contributing independently of STM, KNAT6, and BLR to the process downstream of the CUC genes.…”
Section: Discussionmentioning
confidence: 99%
“…There are five DELLA proteins, namely, REPRESSOR OF ga1‐3 (RGA), GA‐INSENSITIVE (GAI), RGA‐LIKE1 (RGL1), RGA‐LIKE2 (RGL2), and RGA‐LIKE3 (RGL3), in Arabidopsis ; these proteins act as key repressors of the GA response (Peng et al 1997; Silverstone et al 2001; Lee et al 2002; Wen and Chang 2002; Tyler et al 2004). Under LDs, ectopic tissue‐specific expression of DELLAs leads to delayed flowering by inhibiting the expression of flowering time integrator genes such as FT and TWIN SISTER OF FT ( TSF ) in leaves and SPL genes in both the leaves and shoot meristem (Galvão et al 2012; Zhang et al 2020). Expression of gai‐D , a dominant mutant form of the GAI protein (Peng et al 1997) in companion cells resulted in late flowering and reduced FT and TSF messenger RNA (mRNA) levels (Porri et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GA20ox , encoding a GA-biosynthesis enzyme, played various roles in plant development [ 50 ]. Ectopically expressing GA20ox led to an increase in GAs at the leaf axil to inhibit axillary meristem initiation in Arabidopsis [ 42 ]. Our findings showed significant downregulation of AsGA20ox in the stem, suggesting endogenous GAs level at the leaf axil is possibly reduced for activating the process of GA-induced axillary meristem formation.…”
Section: Discussionmentioning
confidence: 99%
“…GA20ox function as a key player in producing bioactive GAs in plants and is cloned from many plant species [ 38 , 39 , 40 , 41 ]. Importantly, a high level of GAs in leaf axils by ectopically expressing GA20ox2 dramatically inhibited axillary meristem initiation in Arabidopsis [ 42 ]. However, it is unknown whether GA20ox expression plays a critical role in GA-induced axillary bud formation of garlic.…”
Section: Introductionmentioning
confidence: 99%